Mechanism of APTX nicked DNA sensing and pleiotropic inactivation in neurodegenerative disease. (22nd June 2018) - Tumbale, Percy; Schellenberg, Matthew J; Mueller, Geoffrey A; Fairweather, Emma; Watson, Mandy; Little, Jessica N; Krahn, Juno; Waddell, Ian; London, Robert E; Williams, R Scott
Abstract: The failure of DNA ligases to complete their catalytic reactions generates cytotoxic adenylated DNA strand breaks. The APTX RNA‐DNA deadenylase protects genome integrity and corrects abortive DNA ligation arising during ribonucleotide excision repair and base excision DNA repair, and APTX human mutations cause the neurodegenerative disorder ataxia with oculomotor ataxia 1 (AOA1). How APTX senses cognate DNA nicks and is inactivated in AOA1 remains incompletely defined. Here, we report X‐ray structures of APTX engaging nicked RNA‐DNA substrates that provide direct evidence for a wedge‐pivot‐cut strategy for 5′‐AMP resolution shared with the alternate 5′‐AMP processing enzymes POLβ and FEN1. Our results uncover a DNA‐induced fit mechanism regulating APTX active site loop conformations and assembly of a catalytically competent active center. Further, based on comprehensive biochemical, X‐ray and solution NMR results, we define a complex hierarchy for the differential impacts of the AOA1 mutational spectrum on APTX structure and activity. Sixteen AOA1 variants impact APTX protein stability, one mutation directly alters deadenylation reaction chemistry, and a dominant AOA1 variant unexpectedly allosterically modulates APTX active site conformations. Synopsis: Aprataxin (APTX) deadenylase protects genomic integrity by reversing DNA adenylation arising during ribonucleotide excision and base excision repair. New structures of APTX‐substrate complexes reveal the mechanism of nicked DNA sensing and the basis for differential impact of APTX mutations in neurodegenerative disorder. Molecular snapshots of APTX in complex with nicked RNA‐DNA substrates show that APTX bends DNA. X‐ray and NMR data define APTX conformations throughout its reaction cycle, supporting a substrate‐induced fit active site assembly mechanism. A wedge‐pivot‐cut strategy for 5′‐AMP resolution is shared with the alternate 5′‐AMP‐processing enzymes POLβ and FEN1. Comprehensive survey of APTX mutations in Ataxia with Oculomotor Apraxia 1 (AOA1) shows their differential impact on APTX protein stability, deadenylation reaction chemistry, and APTX active site conformational changes. Abstract : Structures of Aprataxin deadenylase engaging nicked RNA‐DNA substrates uncover shared strategies with POLβ and FEN1, and the basis for differential impact of APTX mutations in Ataxia with Oculomotor Ataxia 1 (AOA1).